The Effect of Bovine Colostrum Supplementation in the Management of Respiratory Allergies in Children According to Allergen Sensitization: A Subgroup Analysis from the Results of a Randomized Double-blinded Placebo-Controlled Trial - Oloroso-Chavez, Kathleen; Gozalez-Andaya, Pilar Agnes; Wong-Chuah, Cecil (Philippine Journal of Allergy, Asthma and Immunology, 2022)
Introduction: Bovine colostrum supplementation has been shown to significantly reduce nasal allergy symptoms and improve lung function compared with placebo. The authors present a subgroup analysis to determine its effect on the management of respiratory allergies in monosensitized versus polysensitized children. Methodology: The randomized controlled trial was conducted on children aged 7 to 18 years with respiratory allergies who were randomly assigned to receive bovine colostrum 1000 mg (n=19) or placebo (n=19) daily for three months. Total nasal symptoms score (TNSS), asthma control test (ACT), composite asthma severity index (CASI), and pulmonary function test were used to assess symptom improvement for six months. Subgroup analysis was done, and children were categorized into monosensitized and polysensitized groups. Results: The subset of monosensitized patients in the bovine colostrum group showed significant improvement in nasal congestion (p=0.004). For both ACT and CASI scores, significant improvements from beginning to end were demonstrated in the scores of polysensitized children who were given bovine colostrum (p = 0.011 and p = 0.018, respectively). Improvement in lung function test was significantly observed in monosensitized patients given bovine colostrum supplement at the first month (FEV1), second month (FEF25-75 and PEF), and third month (all parameters except FVC) of assessment. In the polysensitized subgroup, only FEV1/FVC ratios at baseline and week two were found significantly improved in the bovine colostrum group (n = 9) than in the placebo group (n = 11). Conclusion: Sensitization can affect an individual’s response to bovine colostrum supplementation. Bovine colostrum supplementation significantly improved nasal congestion in monosensitized patients with respiratory allergies. The ACT and CASI scores significantly improved in polysensitized patients. Lung function response was more visible in monosensitized patients.